Kombinasi Fisher Yates Shuffle dan Bubble Sort Pada Aplikasi Ujian Berbasis Web - Alen Prastya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract – During the current pandemic, educational institutions are implementing an online learning system. The exam process also uses an online system, so that during the exam supervision it cannot be done directly. This study applies the Fisher-Yates Shuffle (FYS) algorithm for the randomization of questions in a web-based exam application with the aim of minimizing collaboration between students. While Bubble Sort is used to sort the questions in descending order with the aim of getting the latest questions from the database. The form of testing is to measure the time used by the two algorithms to perform the randomization (FYS) and sorting (Bubble Sort) processes. The average data speed of randomizing data in the order of 100, 200, 300,400, 500 questions is 343 ms, and the average speed of the bubble sort algorithm with the same data is 433 ms.